Role for Emulsan in Growth of Acinetobacter calcoaceticus RAG-1 on Crude Oil - Pines, O. (1986)
When Acinetobacter calcoaceticus RAG-1 was grown together with an emulsan-deficient mutant on crude oil, only the emulsan-producing RAG-1 was found to grow, regardless of whether the medium was supplemented with emulsan. The results suggested that the cell-associated form of the bioemulsifier is the biologically active species required for growth on crude oil. A revertant of an emulsan-deficient strain was isolated which simultaneously regained the ability to produce both cell-associated and cell-free emulsan as well as the ability to grow on crude oil.